Odpowiedź :
7x-y=-17/6
5x+6y=8
42x-6y=-102
5x+6y=8
-----------
47x=-94/:(47
x=-2
7*(-2)-y=-17
-14-y=-17
-y=-17+14
-y=-3/(-1)
y=3
x=-2
y=3
5x+6y=8
42x-6y=-102
5x+6y=8
-----------
47x=-94/:(47
x=-2
7*(-2)-y=-17
-14-y=-17
-y=-17+14
-y=-3/(-1)
y=3
x=-2
y=3
7x-y=-17 /*6
5x+6y=8
42x-6y=-102
5x+6y=8
42x-6y+5x+6y=-102+8
47x=-94 /:47
x=-2
x=-2
5*(-2)+6y=8
x=-2
-10+6y=8
x=-2
6y=8+10
x=-2
6y=18 /:6
x=-2
y=3
5x+6y=8
42x-6y=-102
5x+6y=8
42x-6y+5x+6y=-102+8
47x=-94 /:47
x=-2
x=-2
5*(-2)+6y=8
x=-2
-10+6y=8
x=-2
6y=8+10
x=-2
6y=18 /:6
x=-2
y=3